Numerical simulation of cross-flow in a bank of tubes with three rows in the subcritical region of Reynolds - Suzairin, (2013)
The present work focused on 2-dimensional unsteady numerical simulation in predicting hydrodynamics and thermal characteristics of air flow across circular tube banks with integral wake splitters. The tube banks studied consist of three rows of tubes in staggered arrangement. The lengths of the splitter are 0, 0.5, 1.0, 1.5 and 2.0 times the tube diameter. The range of Reynolds number investigated is in the range of 1000 to 10000, which is in the sub-critical region of Reynolds number. The flow condition within this range is incompressible since the maximum Mach number is less than 0.3. The numerical approach was validated against the experimental works of Zukauskas (1985) and Anderson (1997). Local pressure coefficient for flow around a single tube with integral wake splitter is also presented for comparison. It was found that the present of the wake splitters was able to improve the overall heat transfer of the system. Â© Published under licence by IOP Publishing Ltd.